Energy Management for Hybrid Energy Storage System in Electric Based on Deep Deterministic Policy Gradient - Xia, Shuai; Wang, Chun (International Journal of Computer Science and Information Technology, 2024)
In this paper, an intelligent control system design scheme based on deep deterministic policy gradient (DDPG) algorithm is proposed for the complex continuous action space problem in the hybrid energy storage system of electric vehicles. Firstly, the basic principle and internal logic of DDPG algorithm are introduced, including key elements such as Actor-Critic architecture, experience playback, target network, reward signal, policy gradient and value function update. Then, how to apply the DDPG algorithm to the industrial control system is described in detail. The Actor network learns the optimal strategy, the Critic network evaluates the value of the state-action pair, and uses the experience playback and the target network to improve the system stability and performance. Finally, the effect of the intelligent control system based on DDPG algorithm in complex environment is verified by simulation experiments. The results show that the system can effectively optimize the control strategy, improve the response speed and stability of the system, and has a good engineering application prospect.